2011
DOI: 10.4269/ajtmh.2011.09-0601
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the 56 kDa Protein Genes of Orientia tsutsugamushi in Southwest Area of Korea

Abstract: This study was conducted to determine which genotypes were present in southwestern Korea. Nested polymerase chain reaction (PCR) and DNA sequence analysis targeting the Orientia tsutsugamushi-specific 56-kDa protein gene was performed with samples of blood and eschar. Of the 69 PCR-positive samples, 61 clustered with the Boryong previously isolated in Korea. CUH 4-6 had sequence homology of 100% with Kato, and CUH 4-3 had homology of 99.8% with Kato and formed the Kato cluster. CUH 4-57, CUH 4-31, CUH 4-142, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…4,9 In addition, Kato, Neimeng-65, and Kawasaki genotypes have been identified in South Korea. 10 Although a prior study reported that the Boryong genotype rather than the Karp genotype predominated on Jeju Island, 7 we found that the Taguchi type was also common on Jeju Island. Previously, reports indicated that the Taguchi genotype is uncommon in endemic areas and does not show clinical manifestation.…”
contrasting
confidence: 66%
“…4,9 In addition, Kato, Neimeng-65, and Kawasaki genotypes have been identified in South Korea. 10 Although a prior study reported that the Boryong genotype rather than the Karp genotype predominated on Jeju Island, 7 we found that the Taguchi type was also common on Jeju Island. Previously, reports indicated that the Taguchi genotype is uncommon in endemic areas and does not show clinical manifestation.…”
contrasting
confidence: 66%
“…These 3 disease entities represent major infectious diseases that occur between September and December, and pose challenges related to differential diagnosis during the autumn season. The genotypic distribution in the southern district of Korea included Boryong (88.4z), Kato (2.9z), Kawasaki (5.8z), Jecheon (1.4z), and Neimeng-65 (1.4z) (18). Another report on the genotypic distribution of O. tsutsugamushi strains that cause human infections in South Korea listed Boryong (68.6z), Taguchi (19.6z), Kanda/Kawasaki (9.2z), Jecheon (1.3z), and UAP7 (1.3z) (19).…”
mentioning
confidence: 99%
“…19 However, serotyping is time-and labor-consuming, and it is limited by the need to include all prototype strains when testing a new strain. Therefore, molecular typing methods, particularly PCR amplification of the 56 kDa protein gene, followed by sequencing have been used extensively for investigations of genotypes of scrub typhus [20][21][22] ; 56 kDa type-specific antigen, which contains both group-and type-specific epitopes, has proven to be more useful for differentiating between O. tsutsugamushi strains. [23][24][25] A previous study by Yu and others 13 showed that sequences from three samples were identical, with a homology of 96% with Kawasaki type, which was the same as the samples analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%